ANALISIS DEMOKRASI HABERMAS PADA TEKS FORUM DISKUSI ONLINE RUU OMNIBUS LAW (JIKE : Jurnal Ilmu Komunikasi Efek, 2020)
According to habermas, public space is a space where citizens can negotiate about their relations so that it is an institutional arena for interaction.  The development of increasingly advanced communication media has resulted in a large amount of public space being carried out online through social media to discuss public issues with the aim of creating a democracy.  This study aims to determine the analysis of habermas democracy in the text of the online discussion forum of the omnibus law ruu as democracy.  The labor law omnibus is still a polemic in the community because on the one hand it is considered to be beneficial for employers and increasingly marginalizes workers / laborers with an hourly wage system plan which is considered by workers to weaken the position and welfare of workers / workers.  This research uses analytical methods in the perspective of communication on deliberative democracy and based on two habermas theories of Structural Transformation of Public Spaces & Between Facts and Norms.  This discourse analysis model is based on 3 blades of communicative action analysis that includes 3 claims.  The data collection technique is a text method in the form of opinions submitted by members of the online discussion group "Work Draft Bill: Threatening Indonesian Employment and Agriculture" and "Work Draft Bill: Breaking Through Indonesian Law?".  Each argument / opinion is analyzed based on three validity claims, namely: truth.  accuracy, and honesty.  The results of this study are based on text analysis that burdensome parties from laborers, students, farmers, fishermen, indigenous peoples, rural and urban residents, and prioritizes the interests of investors and entrepreneurs